Evaluation of cases of pemphigus vulgaris and pemphigus foliaceus from a reference service in Pará state, Brazil - PIRES, Carla Andréa Avelar (2015)
BACKGROUND: Pemphigusis a bullous, rare and chronic autoimmune disease. There are two major forms of pemphigus: vulgaris and foliaceus. Epidemiological data and clinical outcome in patients diagnosed in the Brazilian Amazon states are still rare. OBJECTIVES: To study the occurrence of the disease during the study period and analyze the epidemiological profile of patients, the most common subtype of pemphigus, and the clinical evolution of patients. METHODS: Retrospective analysis of medical records of hospitalized patients with pemphigus foliaceus and pemphigus vulgaris in the period from 2003 to 2010 in Dermatology Service of Hospital Fundação Santa Casa de Misericórdia do Pará, Belém, Northern Brazil. RESULTS: We found a total of 20 cases of pemphigus during the study period, 8 of which were of foliaceus pemphigus and 12 of vulgaris pemphigus. Pemphigus foliaceus had the predominance of male patients (75%), showed satisfactory clinical evolution, and was characterized by absence of pediatric cases. Pemphigus vulgaris affected more women (66.7%), showed mean hospital stay of 1 to 3 months (50%), and there were three cases of death (25%). The prescribed immunosuppressive drugs included prednisone with or without combination of azathioprine and/or dapsone. Sepsis was associated with 100% of the deaths. CONCLUSIONS: The occurrence of the disease is rare, there are no familiar/endemic outbreaks in the sample. Evolution is usually favorable, but secondary infection is associated with worse prognosis. The choice of best drugs to treat pemphigus remains controversial.